1999
DOI: 10.1111/j.1600-0668.1999.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

House Dust Induces IL-6 and IL-8 Response in A549 Epithelial Cells

Abstract: The in vitro potency of house dust to induce cytokine response in A549 lung epithelial cells was studied. Dusts collected from carpet, bed, shelf and floor of a villa and an apartment by vacuuming were found to trigger the production of interleukin-8 (IL-8) and interleukin-6 (IL-6) in a dose-dependent manner, and the interleukin production was several-fold higher than of swine dust (used as a positive control). The IL-8 and IL-6 production of pure Escherichia coli lipopolysaccharide was significantly lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…Therefore, and keeping earlier considerations 25 in mind, we concluded that the observations made here were applicable to the rural population in the countries in which the study took place, and may not be extrapolated to urban populations. Muramic acid concentrations found in our study (geometric mean, 128 ng/mg) were somewhat higher when compared with previously reported concentrations of 23.1 ng/mg and 50.5 ng/mg dust from 2 beds, 22 and were much higher than concentrations found by Liu et al 20 in floor dust from schools. These differences are probably in part attributable to methodological differences in sampling or analysis and to differences between school floors and mattresses.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Therefore, and keeping earlier considerations 25 in mind, we concluded that the observations made here were applicable to the rural population in the countries in which the study took place, and may not be extrapolated to urban populations. Muramic acid concentrations found in our study (geometric mean, 128 ng/mg) were somewhat higher when compared with previously reported concentrations of 23.1 ng/mg and 50.5 ng/mg dust from 2 beds, 22 and were much higher than concentrations found by Liu et al 20 in floor dust from schools. These differences are probably in part attributable to methodological differences in sampling or analysis and to differences between school floors and mattresses.…”
Section: Discussioncontrasting
confidence: 75%
“…[17][18][19] Several occupational environments, like swine confinement buildings, 17 a dairy, 18 2 schools, 20 and several other places with exposure to organic dust, 19 have been studied. Few studies are available on determinants of muramic acid in house dust, [21][22][23] and no data are available on health effects of muramic acid/peptidoglycan. The determination of muramic acid may be more representative than endotoxin in estimating the total microbial burden; there is also some evidence that peptidoglycan influences the innate immune system.…”
mentioning
confidence: 97%
“…To measure the TIP of indoor dust different cell based in vitro assays have been used based on the Human Promyelocytic Leukaemia cell line (HL-60) [21] a human macrophage cell line [33], a lung epithelial cell line (A549) [3,33,51]. The detailed procedure and evaluation of TIP (TIP m À2 day À1 ) of settled dust is described in Refs.…”
mentioning
confidence: 99%
“…For example, human epithelial cells have been used to measure induction of interleukin-6 and interleukin-8 production by house dust samples. Elevated levels of these inflammatory markers were observed with house dust, while swine dust or pure endotoxin gave no such response (Saraf et al, 1999). THP-1 monocytic cell line has been suggested as another sensitive bioassay and potential screening tool for hazard evaluation of settled dust in the indoor environment (Allerman and Poulsen, 2002).…”
Section: Other Methods To Detect Biological Materialsmentioning
confidence: 99%